Development Characteristics and Enlightenment of Inclusive Early Childhood Education in the United States - Han, Wei (Transactions on Social Science, Education and Humanities Research, 2023)
Inclusive education is a continuous educational process, that is, accepting all students, opposing discrimination and exclusion,promoting active participation, focusing on collective cooperation and meeting different needs. Inclusive education is a new trend of thought in international education, which originated in the Civil Rights Movement in1950s. American inclusive education has gone through three stages of development: returning to mainstream education, supporting special education actively by general education,and inclusive education. Three forms of integration are adopted: full integration, semi-integration and reverse integration. The outstanding feature is that the Government has enacted laws and policies to guarantee children's equal access to education, and to meet the different development needs of children by providing education that gives adequate assistance and support to all children.The development of inclusive preschool education in our country needs to be carried out from the aspects of concept, teachers,policies,parents,funds and so on.